Factors affecting birth weight in Cape Coast, Ghana - Prah, James; Ameyaw, Elvis O.; Afoakwah, Richmond; Kudom, Andreas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study aimed at determining the incidence of low birth weight among live births and maternal anaemia and to investigate the association between some maternal factors and birth weight. Methods: This was a retrospective cross sectional study that involved mothers who regularly attended antenatal clinics and had delivered singleton live births between January 2014 to December 2014 in the University of Cape Coast Hospital, Cape Coast, Ghana. Results: Out of the 405 newborns included in the study, 194 (47.90%) were females and 211 (52.10%) males with a mean birth weight of 3.25±0.52kg. There was a low birth weight prevalence of 7.7% and a maternal anaemia prevalence of 38.8%. The period of gestation (p=0.00001), maternal anaemia (p=0.0217) and maternal age (p=0.0030) were found to be significantly associated with birth weight. Sex of baby (p=0.6668), parity of mother (p=0.6959) and maternal sickling status (p=0.7915) were not significantly associated with birth weight. Conclusions: As far as low birth weight is concerned, frequency is not high among live babies born to mothers who regularly attended antenatal clinics. This agrees with studies that suggest that antenatal clinic attendance positively affects birth weight. Thus in order to reduce the high prevalence of low birth weight and maternal anaemia in developing countries all pregnant women must be encouraged to attend antenatal clinics regularly.